A SEMIOTIC STUDY ON INDONESIAN DRAMA MOVIE POSTERS UNDER RELIGION DIFFERENCE THEME - KAFITASARI, INTAN (Jurnal Ilmiah Mahasiswa FIB, 2013)
This research is aimed to find out the category of signs and figure out the meaning of signs found in the posters of Cin(T)a (2009), 3 Hati Dua Dunia Satu Cinta 2010), "?" (2011) and Cinta Tapi Beda (2012) movies in which all of them have the same theme, that is religion difference. This research discovers that the icon, index and symbol are found in the posters. The iconic signs are mostly applied. The indexical signs are found more than the symbolic one. The meaning of signs is related to the story of the movie and certain cases happen in the society since the theme of the movie is the reflection of the real condition of Indonesian society. In accordance with the analysis, the signs that represents religion difference are still blurry in the first movie poster entitled Cin(T)a. The next three posters are clearer in representing the difference of religion. The last movie entitled Cinta Tapi Beda has the poster that is considered as the clearest one. Keywords:movie poster, sign, connotation, icon, index, symbol.